PSIV-6 Differential gene expression of fibro/adipogenic progenitors between Wagyu and Brahman cattle: A possible contribution to their different meat quality. (8th October 2021) - Li, Chaoyang; Liu, Qianglin; Welborn, Matt; Wang, Leshan; Li, Yuxia; Deng, Buhao; McMillin, Kenneth; Fu, Xing
Abstract: The amount of intramuscular fat directly influences the meat quality. However, significant differences in the ability to accumulate intramuscular fat are present among different beef cattle breeds. While Wagyu, a cattle breed that originated from Japan, is renowned for abundant intramuscular fat, Brahman cattle generally have very little intramuscular fat accumulation and produce tougher meat. We identified that bovine intramuscular fat is derived from a group of bipotent progenitor cells named fibro/adipogenic progenitors (FAPs) which also give rise to fibroblasts. Thus, the variation in intramuscular fat development between Wagyu and Brahman is likely attributed to the difference in FAPs between these two breeds. In order to understand the gene expression difference between FAPs of the two breeds, single-cell RNA-seq was performed using total single-nucleated cells isolated from the longissimus muscle of young purebred Wagyu, purebred Brahman, and Wagyu-Brahman cross cattle. FAPs constitute the largest single-nucleated cell population in both Wagyu and Brahman skeletal muscle. Multiple subpopulations of FAPs with different gene expression profiles were identified, suggesting that FAP is a heterogeneous population. A unique FAP cluster expressing lower levels of fibrillar collagen and extracellular remodeling enzyme genes but higher levels of select proadipogenic genes was identified exclusively in Wagyu skeletal muscle, which likely contributes to the robust intramuscular adipogenic efficiency of Wagyu FAPs. In conclusion, the difference in the cellular composition and gene expression of FAPs between Wagyu and Brahman cattle likely contribute to their distinct meat quality.